2017
DOI: 10.1016/j.soildyn.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Seismic wave amplification by topographic features: A parametric study

Abstract: Despite the ever increasing adoption of wave motion simulations for assessing seismic hazard, most assessment/simulations are still based on a flat surface earth model. The purpose of this paper is to quantify the effect of topographic irregularities on the ground motion and local site response by means of parametric investigations in the frequency-domain of typical two-dimensional features.To this end, we deploy best-practice tools for simulating seismic events in arbitrarily heterogeneous formations; these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…S17). Several authors have shown that ridge sharpness promotes topographic amplification (Maufroy et al, 2015;Rai et al, 2016). The landslide position would thus reflect the expression of strong ground motion in the uppermost part of the slope, which can be explained by complex interactions of various seismic waves with both topography and lithology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S17). Several authors have shown that ridge sharpness promotes topographic amplification (Maufroy et al, 2015;Rai et al, 2016). The landslide position would thus reflect the expression of strong ground motion in the uppermost part of the slope, which can be explained by complex interactions of various seismic waves with both topography and lithology.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations of ground shaking in complex topographies predict that seismic waves are actually amplified around ridge crests (e.g. Boore, 1973;Massa et al, 2014;Poursartip et al, 2017). Both seismic noise analysis and strong motion records confirm that stronger shaking often occurs at topographic highs (Chávez-García et al, 1996;Durante et al, 2017;Hartzell et al, 2014;Massa et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…The static and dynamic parameters of the dam are shown in Table 2 and Table 3, in which # 1 is the major rock-fill zone and # 2 is the minor rock-fill zone, which are obtained by experimental results [22,23]. The contact parameters are presented in Table 4, where #3 is the contact surface between the panel and the dam, and #4 is the contact surface between the cut-off wall and the cover [24]. To highlight the single factor of the overburden thickness, homogeneous sand was selected as the overburden material, with the following mechanical parameters: natural dry density ( ) of 2.2 g•cm −3 , deformation modulus ( ) of 50 MPa, and friction angle ( ) of 38°.…”
Section: Materials Parametersmentioning
confidence: 99%
“…Huang et al [20,21] analyzed the impacts of incident angles on the seismic behavior of the long-lined tunnel buried in an elastic half-space. Poursatip et al [22,23] numerically studied the effects of topographic irregularities on the ground motion and local site response under obliquely incident P and SV waves in the frequency domain and elastic half-space. As seen, most prior studies either simplified the soil media as a uniformly elastic half-space when conducting numerical simulations, or analytically solved the problem in the frequency domain to account for the layered condition.…”
Section: Introductionmentioning
confidence: 99%